Down-Regulation of ABCA7 in Human Microglia, Astrocyte and THP-1 Cell Lines by Cholesterol Depletion, IL-1β and TNFα, or PMA - Joel P. Wiener; Sindy Desire; Viktor Garliyev; Nicholas Lyssenko III; Domenico Praticò; Nicholas N. Lyssenko (Cells, 2023)
Adenosine triphosphate-binding cassette transporter subfamily A member 7 (ABCA7) is a major risk factor for Alzheimer’s disease. Human neural cell lines were used to investigate the regulation of ABCA7 expression by cholesterol and pro-inflammatory cytokines. Cholesterol was depleted by methyl-β-cyclodextrin, followed by treatment with rosuvastatin to suppress de novo synthesis, while the cells underwent adjustment to low cholesterol. Cholesterol depletion by 50–76% decreased ABCA7 expression by ~40% in C20 microglia and ~21% in A172 astrocytes but had no effect on the protein in SK-N-SH neurons. Cholesterol depletion also suppressed ABCA7 in HMC3 microglia. Previously, cholesterol loss was reported to up-regulate ABCA7 in murine macrophages. ABCA7 was down-regulated during PMA-induced differentiation of human THP-1 monocytes to macrophages. But, cholesterol depletion in THP-1 macrophages by ~71% had no effect on ABCA7. IL-1β and TNFα reduced ABCA7 expression in C20 and HMC3 microglia but not in A172 astrocytes or SK-N-SH neurons. IL-6 did not affect ABCA7 in the neural cells. These findings suggest that ABCA7 is active in regular homeostasis in human neural cells, is regulated by cholesterol in a cell type-dependent manner, i.e., cholesterol depletion down-regulates it in human neuroglia but not neurons, and is incompatible with IL-1β and TNFα inflammatory responses in human microglia.